Enterprise information systems assurance and system security managerial and technical issues - Warkentin, Merrill; Vaughn, Rayford 1947- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2006)
"This book brings together authoritative authors to address the most pressing challenge in the IT field - how to create secure environments for the application of technology to serve our future needs"--Provided by publisher